TOPICAL FORMULATION CONSTITUTED WITH TRANSFEROSOMES FOR THE TREATMENT OF NON-MELANOMA SKIN CANCER - IMAM, SYED SAIF (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Overexposure to UV-B radiation causes an evolution in the strands of DNA of skin membrane cells, resulting in non-melanoma skin cancer. With the addition of excipients and nanovesicular structures such as transferosomes that boost the permeability rate and pharmacological activity, a formulation containing curcumin, kaempferol, trans-resveratrol, and apigenin have been developed which possess strong anti-inflammatory and anti-proliferative potential. The formulation quickly penetrates the stratum corneum and acts on cancer cells, inhibiting metastasis and angiogenesis by interfering with signaling molecules in the three primary mitogen-activated protein kinase pathways: extracellular-signal-regulated kinase, c-Jun N-terminal kinases, and p38. It blocks pro-inflammatory cytokines such as lipopolysaccharide, tumor necrosis factor-alpha, IL1, IL6, COX-2, LOX, oxidative stress, and lowers the levels of matrix metalloproteinase (MMP)-3, MMP-9, and vascular endothelial growth factor. The yield value, sensory testing, spreadibility, dynamic viscosity, water content, pH, specific gravity, anti-microbial preservative concentration, microbiological limit, sterility testing, contaminants, uniformity of dosage, and assay on RAW264.7 cell line will all be used to evaluate the formulation. The O/W cream that has been produced will be significantly more successful than traditional cancer treatments, and it will have no side effects, protects the patient from recurrence of cancer and inexpensive treatment.